The boy in the woods : a true story of survival during the Second World War - Smart, Maxwell (2022)
"A heart-wrenching story of a boy on his own in Second World War Europe, forced to fend for himself in the woods When the Nazis and Ukrainians invaded Buczacz, Poland in 1941, Oziac Fromm's happy boyhood changed forever. The Jewish boy lost 62 members of his family in only a short period of time. He survived by, at his mother's bidding, taking the yellow star off his clothing and walking across the bridge and out of town as if he were any other Pole. He eventually found shelter in a hole in the woods, spending many months on his own until a younger boy, Janek, wandering alone after everyone he had been hiding with had been killed, joined him. After a nearby massacre, the boys discovered and rescued a baby, still alive in the frozen arms of her dead mother. The rescue came at great cost, however, as Janek died from hypothermia, and Oziac was again alone and bereaved. Oziac would survive the war, and over many months, still only a teenager, he made his way around Europe, trying to make a small living in fractured post-war Europe. Oziac would eventually make his way to Montreal, where he married, started a family, and followed his passion for art, painting and drawing to soothe his troubled soul. He would eventually open a small gallery and sell his paintings and had by then changed his name to the more Canadian-sounding Maxwell Smart. He is now a highly respected businessman and artist, thriving at the age of 90. Only recently, Smart met up with Janek's family, an emotional reunion captured in moving prose, and he also met up with the woman who had been that baby he had saved, meeting the generations of her family who would never have been without his intervention. The Boy in the Woods is testament to the human spirit, and a remarkable historical document about a time that should never be forgotten.